2018
DOI: 10.3390/ijerph15112419
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Endocrine Disrupting Chemicals from Water: Adsorption of Bisphenol-A by Biobased Hydrophobic Functionalized Cellulose

Abstract: The aim of this study is to examine the efficiency of biobased Spanish broom (SB) surface modified cellulose fibers to remove bisphenol A (BPA), a well-known endocrine disruptor, from water. Spanish brooms are flowering plants, which are native and abundant to Mediterranean regions. The functionalized fibers (FF) were found to have the best adsorption efficiency at pH 5, due to the optimal hydrophobic interaction between the FF fiber and BPA. Adsorption kinetics of BPA was found to fit well a pseudo-second ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Several review papers on biological treatment of winery wastewater have cited the imbalance of COD:N:P as an impediment for carbon removal, with nitrogen and phosphorus as the limiting nutrients [6,66,76]. The ratio of COD:N in winery wastewater is often 100, an order of magnitude larger than that in municipal wastewater [6,77]. As such, nitrogen and phosphorus are expected to have higher removal efficiencies as microbes use up these nutrients for biosynthesis.…”
Section: Appl Sci 2020 10 X For Peer Reviewmentioning
confidence: 99%
“…Several review papers on biological treatment of winery wastewater have cited the imbalance of COD:N:P as an impediment for carbon removal, with nitrogen and phosphorus as the limiting nutrients [6,66,76]. The ratio of COD:N in winery wastewater is often 100, an order of magnitude larger than that in municipal wastewater [6,77]. As such, nitrogen and phosphorus are expected to have higher removal efficiencies as microbes use up these nutrients for biosynthesis.…”
Section: Appl Sci 2020 10 X For Peer Reviewmentioning
confidence: 99%
“…It has been recently shown that these fibers can be used either in the pristine form to remove inorganic contaminants from water 21 or, after surface functionalization, organic pollutants from water by adsorption processes. 22,23 Here, we have explored the possibility to use a low pressure plasma sputtering technique for the deposition of TiO2 on Spanish Broom cellulose surface. Generally, non-equilibrium plasma processes, both at low or atmospheric pressure, are ecofriendly, versatile and, thanks to their low temperature (near to room), allow the modification of the uppermost layers of flat substrates, 24 fibers or granules, [25][26][27][28][29] without changing their bulk properties.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the adsorption of water-dissolved pollutants by means of natural fibers represent an effective alternative to the aforementioned methods. Cellulosic and lignocellulosic fibers [4,[32][33][34][35][36][37][38] are cost-effective reagents resulting from the use of low-cost or waste materials. The high adsorbing capacity of these natural fibers is attributable to the presence of interfiber capillaries and a considerable specific surface area (SSA).…”
Section: Introductionmentioning
confidence: 99%
“…The absence of secondary products during their application and the possibility for their re-use several times imply a low environmental impact. Nevertheless, the biggest advantage lies in the possibility of fiber surface functionalization using sustainable methods: the presence of reactive hydroxyl groups emerging from the fiber surface [41] allows us to add specific functional sites (which correspond to the pollutant absorption sites), with the aim of increasing the affinity and/or selectivity of the adsorbent material for the contaminant to be removed from water [36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%